Recent Advances in the Synthesis of Nitrogen Heterocycles Using Arenediazonium Salts as Nitrogen Sources. Issue 22 (24th August 2020) - Liu, Jidan; Jiang, Jinyuan; Zheng, Liyao; Liu, Zhao‐Qing
Abstract: Nitrogen heterocycles are important structural subunits that occur widely in bioactive natural products, pharmaceuticals, agrochemicals, dyes, cosmetics, and functional materials. Considering the importance of these useful compounds in modern science, the synthesis of N‐heterocycles and their derivatives has always been a hot topic in organic synthesis. Recently, arenediazonium salts which can be easily prepared from inexpensive and abundantly available anilines, have been used as versatile nitrogen sources in the field of nitrogen heterocycle synthetic chemistry due to their ready availability, rich reactivity, and diverse transformations. The aim of the present review is to summarize the recent advances in the synthesis of nitrogen heterocycles using arenediazonium salts as nitrogen sources in the past ten years. Hopefully, it can provide practical guidance for the readers who are interested in utilizing arenediazonium salts as building blocks in organic synthesis. For simplicity and clarity, the organization of this review is based on the number of N atoms in the ring of nitrogen heterocycle. Abstract :